2005
DOI: 10.1002/jbm.a.30240
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response to collagen after functional implantation of different polyester vascular prostheses in pigs

Abstract: Besides inflammation, specific immune responses are seen also after implantation of biomaterials. The aim was to investigate the humoral response to bovine collagen type I following implantation of various polyester (Dacron) prostheses into pigs. In 24 randomized pigs, the infrarenal aorta was replaced with a segment of collagen-impregnated, woven polyester prosthesis of low, medium, or high porosity. IgG antibodies were detected by immunoassay using native and denatured collagen type I as a target for blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…The simultaneous implantation of the four implants into the same individual animals as performed in this study was similar to previous experiments on calcium-phosphate-coated titanium [14]. The advantage of this approach is that it eliminates the broad individual variability of host reactions which were observed, for example, in studies on the immunological reactions against vascular prostheses using inbred rats as well as pigs [16,17].…”
Section: Discussionmentioning
confidence: 81%
“…The simultaneous implantation of the four implants into the same individual animals as performed in this study was similar to previous experiments on calcium-phosphate-coated titanium [14]. The advantage of this approach is that it eliminates the broad individual variability of host reactions which were observed, for example, in studies on the immunological reactions against vascular prostheses using inbred rats as well as pigs [16,17].…”
Section: Discussionmentioning
confidence: 81%
“…[1][2][3][4][5][15][16][17][18] ECM molecules such as type I collagen, laminin, and fibronectin of xenogeneic origin were found to be immunogenic in mammals and induce antibody production. [19][20][21] Thus, it is possible that antibodies produced by the recipient against ECM molecules bind to implanted ECM and hinder by their physical presence the stem cell/ECM interaction. In addition, such ECM-bound antibodies may prevent stem cells interaction with specific ligands on the ECM.…”
Section: Detrimental Effects Of Anti-ecm Antibodiesmentioning
confidence: 99%
“…Polyesters and polyanhydrides, as well as other similarly structured polymers, degrade via hydrolysis and give rise to products with carboxylic acid terminal groups. Thus their degradation may create an acidic regenerative environment which can prolong the inflammatory response and accelerate the degradation of the material, leading to premature loss of mechanical and structural properties (54,55). Previous studies have also shown that accumulation and increased concentration of acidic degradation products can induce tissue toxicity (28,29,56).…”
Section: Polyanhydridesmentioning
confidence: 99%